Exploring Parenting Styles and Their Impact on Child Development in the Community (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2022)
This research explores the relationship between parenting styles and child development in the community context. It delves into the various parenting styles, including authoritarian, democratic, permissive, and others, and examines their distinctive characteristics and effects on children's physical, emotional, social, and cognitive development. The study acknowledges the significance of the family environment in shaping a child's growth and development. It emphasizes that positive parenting practices, such as a balanced and democratic approach, tend to foster a healthy and independent developmental trajectory. However, it also underscores the influence of various factors such as culture, education, personal experiences, and socioeconomic context in determining parenting choices and practices. Furthermore, the research highlights the role of the broader community and the surrounding environment in influencing parenting styles. It discusses how schools, peer groups, and media contribute to the formation of parenting patterns. The practical implications of this research are substantial. The findings can be used to develop parent education programs, psychological support services, and community awareness campaigns aimed at promoting healthy parenting practices. Policymakers can also consider the research outcomes in designing policies that support families in adopting positive parenting approaches. Despite its valuable insights, the study acknowledges certain limitations, including sample constraints and the use of secondary data. Thus, there is room for further in-depth and extensive research in this area. In conclusion, this research significantly contributes to our understanding of parenting styles and their impact on child development in the community. It lays the foundation for efforts to promote healthier parenting practices and better child development in the future